ANALISIS PENGARUH DINING EXPERIENCE DAN PERAN MEDIASI CUSTOMER SATISFACTION TERHADAP BEHAVIORAL INTENTION PADA RESTAURANT TARA CAFE DAN RESTO - Ihsano Aviscenna Fauzul; Jauharry Jauharry (JURNAL MANAJEMEN, 2020)
This study aims to analyze the effect of dining experience analysis mediated by customer satisfaction on behavioral intention at the Tara Café and Resto restaurants in Payakumbuh City. The sample size for this research is 126 respondents. The sampling technique is purposive sampling. Data analysis in this study used Structural Equation Modeling - Partial Least Square (SEM-PLS) and was processed using SmartPLS version 3.0 for windows. The results of the study show that dining experience has a significant and positive influence on customer satisfaction, customer satisfaction does not have a significant and positive effect on behavior intention and dining experience mediated by customer satisfaction has a significant and positive effect on behavioral intention